The Songs That Nearly Got Away: An Examination of the Unpublished Portion of Kenneth Peacock’s Newfoundland Field Collection - Guigne, Anna Kearney (MUSICultures, 2003)
Kenneth Peacock’s Songs of the Newfoundland Outports was and still is a landmark collection of Maritime music. But for several reasons, Peacock did not include in the publication all the songs he had collected. This article examines the reasons for non-inclusion and explores the hidden value of this unpublished music.